Garnet–PVDF composite film modified lithium manganese oxide cathode and sulfurized carbon anode from polyacrylonitrile for lithium-ion batteries. Issue 28 (10th July 2020) - Berhe, Gebregziabher Brhane; Su, Wei-Nien; Abrha, Ljalem Hadush; Bezabh, Hailemariam Kassa; Hagos, Teklay Mezgebe; Hagos, Tesfaye Teka; Huang, Chen-Jui; Sahalie, Niguse Aweke; Jote, Bikila Alemu; Thirumalraj, Balamurugan; Kurniawan, Darwin; Wang, Chia-Hsin; et al.
Abstract : Composite film of polyvinylidene difluoride (PVDF) and Li5.6 Ga0.26 La2.9 Zr1.87 Nb0.05 O12 garnet improves the cycling stability and rate capability of lithium manganese oxide (LMO) cathode. Abstract : Lithium manganese oxide (LMO) is one of the most promising cathode materials for lithium-ion batteries. However, the dissolution of manganese and its deposition on the anode surface cause poor cycling stability. To alleviate these issues, a film composed of polyvinylidene difluoride (PVDF) and Li5.6 Ga0.26 La2.9 Zr1.87 Nb0.05 O12 type garnet (PVDF@LGLZNO) is coated directly on the LMO electrode and it functions as a promising artificial cathode–electrolyte interphase (CEI). The film thickness is optimized taking into account the electrospinning–processing time. To realize a cell with good capacity retention, excellent rate capability and resilience under harsher conditions ( e.g. elevated temperature or high rates), the coated LMO cathode is coupled with a new anode which consists of sulfurized carbon derived from polyacrylonitrile (S-C(PAN)). The electrode (LMO-30 min) coated with the PVDF@LGLZNO composite material shows outstanding cycling stability and rate capability, as well as capacity retention when compared to the bare electrode both at room temperature (25 °C) and elevated temperature (55 °C). The PVDF@LGLZNO fibrous film coating suppresses the dissolution of manganese both at high C-rates and 55 °C, as supported by XPS, whereas PVDF coated and bare LMO cathodes are not able to prevent further deterioration of themselves. The film significantly minimizes undesirable side reactions at the cathode–electrolyte interface and reduces charge transfer resistance. The new cell with PVDF@LGLZNO (LMO-30 min) modified cathode and S-C(PAN) anode delivers capacity retention of 77% after 1000 cycles at 1C, corresponding to an average capacity decay of 0.023% per cycle.